Coronavirus disease 2019 pandemic and allogeneic hematopoietic stem cell transplantation: a single center reappraisal - Valentini, Caterina Giovanna (Cytotherapy, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has deeply modified the complex logistical process underlying allogeneic hematopoietic stem cell transplant practices. Aim: In light of these changes, the authors compared data relative to allogeneic transplants carried out from 2018 at their center before (n = 167) and during the pandemic (n = 45). Methods: The authors examined patient characteristics, donor and graft types, cell doses and main transplant outcomes. Moreover, the authors evaluated the rise of costs attributable to additional COVID-19-related procedures as well as the risk of adverse events these procedures conveyed to grafts or recipients. Results: Overall, the number of transplants did not decrease during the pandemic, whereas patients at high relapse risk were prioritized. Transplants were mainly from matched unrelated donors, with a significant decrease in haploidentical related donors. Moreover, the use of bone marrow as a graft for haploidentical transplant was almost abandoned. Cryopreservation was introduced for all related and unrelated apheresis products, with a median storage time of 20 days. Notably, transplant outcomes (engraftment, acute graft-versus-host disease and non-relapse mortality) with cryopreserved products were comparable to those with fresh products. Conclusions: Considering that the emergency situation may persist for months, cryopreserving allogeneic grafts can offer a lifesaving opportunity for patients whose allogeneic transplant cannot be postponed until after the end of the COVID-19 pandemic.